Kinetic and thermodynamic compensation of non-enzymatic browning of clarified lemon juices - Ibarz, Raquel (2024)
This paper presents a study on kinetic and thermodynamic compensation to evaluate the kinetics of non-enzymatic browning of clarified lemon juices. In a previous work, the kinetic constants of browning were presented using the evolution of the absorbance at 420 nm (A420) and luminosity (L*) for different soluble solids contents (64.6; 50; 35; 20 and 10 ºBrix) and different working temperatures (70, 80, 90 and 95 ºC). The parameters of the Arrhenius equation were obtained by fitting the kinetic constants and temperatures. The variation of lnK0 with Ea follows a linear trend, so there is kinetic compensation, with isokinetic temperature values being 126.6 ºC and 149.7 ºC for A420 and L*, respectively. The transition state equilibrium constants were determined using the Eyring equation for each soluble solids content and each temperature. The equilibrium constants were adjusted to the Van't Hoff equation and the set of pairs of estimated values for the activation enthalpy and the activation entropy also followed a straight line, which causes thermodynamic compensation, with isoequilibrium temperatures of 112.8 ºC and 136.3 ºC for A420 and L*, respectively. It was concluded that the browning mechanism is the same for the ranges of soluble solids content and temperature studied. Since all isokinetic and isoequilibrium temperatures were higher than the working temperature values, it was also concluded that the control was enthalpic for all cases. To avoid the deterioration of these juices, it is advisable to intervene in the working temperature, trying to ensure that the heat treatment is carried out at the lowest possible temperature.